"My bisexual 3 years" : a novel book original - Vail, Ann (Chicago: Novel Books, 1963)
"By Ann Vail as told to Con Sellers Fonds Suzan Daniel (FSD)Fonds Suzan Daniel (FSD) F/02/016 Archief Roger Vertongen"